2018
DOI: 10.1002/brb3.1109
|View full text |Cite
|
Sign up to set email alerts
|

Sensory manipulation results in increased dorsolateral prefrontal cortex activation during static postural balance in sedentary older adults: An fNIRS study

Abstract: BackgroundThe dorsolateral prefrontal cortex (DLPFC) is involved with allocating attentional resources to maintain postural control. However, it is unknown whether age‐related structural and functional declines of the DLPFC may impair postural control during sensory manipulation. In this study, we aim to understand the effects of aging on the DLPFC when sensory cues were removed or presented inaccurately (i.e., increased sensory complexity) during the sensory orientation test (SOT).MethodsTwenty young (18–25 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
(61 reference statements)
3
16
0
Order By: Relevance
“…The connections from the DLPFC to the M1 transfer crucial information for the execution of motor output (Cao et al, 2018). The results from Teo et al (2018) highlighted the involvement of the DLPFC in maintaining postural control. Study also demonstrated that the prefrontal cortex (PFC) and temporal-parietal regions were engaged during active balancing process, which was thought to be involved with allocation of attentional demands in standing postural control (Mihara et al, 2008).…”
Section: Introductionmentioning
confidence: 87%
“…The connections from the DLPFC to the M1 transfer crucial information for the execution of motor output (Cao et al, 2018). The results from Teo et al (2018) highlighted the involvement of the DLPFC in maintaining postural control. Study also demonstrated that the prefrontal cortex (PFC) and temporal-parietal regions were engaged during active balancing process, which was thought to be involved with allocation of attentional demands in standing postural control (Mihara et al, 2008).…”
Section: Introductionmentioning
confidence: 87%
“…increase PFC activation with no concomitant increase in functional performance) that was associated with reduced grey matter volume of the PFC with ageing. This effect has been consistently shown in healthy older adults during DTG (Doi et al, 2013;Ohsugi et al, 2013;Mirelman et al, 2017) or balance (Lin et al, 2017;Teo et al, 2018) tasks that require increased attentional demands. What was, therefore, surprising was that people with SMC displayed a higher level of left PFC activation, significantly greater than that of healthy controls, despite no differences in age or MoCA scores between both groups.…”
Section: Stg and Dtgmentioning
confidence: 60%
“…The probes were placed 3 cm away from each other, to monitor the cortical activation over two 9 cm × 9 cm rectangular elds of view. The electroencephalography (EEG) International 10-20 system Cz, C3, C4 anatomical measurements were used as reference points to ensure that the optical probe setup was placed over 6 ROIs (25) , including the bilateral SMC, PMC and PFC. A three-dimensional (3D)-digitizer was used to record the exact locations of each fNIRS probe for a standard brain before converting these coordinates into the locations of the forty-eight channels in an estimated Montreal Neurological Institute (MNI) space using the MATLAB toolbox NIRS-SPM (26).…”
Section: Data Acquisitionmentioning
confidence: 99%